Language as a Tool of Shaping Pro-ecological Attitudes on Polish and Bulgarian Compounds with the Eco- Component in the Journalistic Discourse - Długosz, Natalia (Poznańskie Studia Slawistyczne, 2015)
The article focuses on the selected cognitive aspects of the interpretation of meaning of Polish and Bulgarian compounds with the eco-component in the journalistic discourse. According to the assumptions suggested by J. Bartmiński and S. Niebrzegowska-Bartmińska, I define discourse as „a processual and contextual conceptualization of a «communication event» whose objective «created» conceptualization is text”. I provide the composites present in Polish and Bulgarian journalistic discourse with a critical eco-linguistic comment. The analysis made on texts being the  objective conceptualization  of  the  journalistic  discourse  proves  semantic  under-specification of the eco-component. In many structures, this component loses the meaning content in the sense of denotation, while it carries a certain axiological judgment, becoming a kind of emotive operator that makes it easier to manipulate the meaning.